Sistema web de gestión de evidencias en las unidades de docencia, investigación y vinculación de la ESPAM MFL - Loor Ormaza, Gerardo Francisco (2017)
The purpose of this proposal was to implement a web system in the teaching, research and linking units of ESPAM MFL for the management of evidence, developed with the MIDAS methodology (Interactive Methodology for Software Application Development), which consists of five activities: MIDAS / SD (System Definition), the process was built, requirements were defined and the architecture systems, achieved with an interview; MIDAS / HT (Hypertext), designing prototype HTML5 static pages; MIDAS / DB (Database), modeling the database in Microsoft SQL Server 2012 R2; MIDAS / FC (Functionality), a standard was established to program the web systems in Visual Studio 2013 Ultimate and in MIDAS / TST (Testing), In summary, was verified the good functioning of the web solution, as a result, the system contributes with the evaluation Process about production units also to the making decisions.